A highly efficient heterogeneous copper-catalyzed three-component coupling of tetrahydroisoquinolines, aldehydes and 1-alkynes. Issue 5 (14th October 2015) - Zhao, Hong; He, Wen; Wei, Li; Cai, Mingzhong
Abstract : A highly efficient heterogeneous copper-catalyzed three-component coupling of tetrahydroisoquinolines, aldehydes and 1-alkynes has been described. Abstract : A highly efficient heterogeneous three-component coupling of tetrahydroisoquinolines, aldehydes and 1-alkynes was achieved in toluene at 70 °C in the presence of a 3-(2-aminoethylamino)propyl-functionalized MCM-41-supported copper(i ) complex [MCM-41-2N–CuI], yielding a variety of C1-alkynylated tetrahydroisoquinolines ( endo -yne-THIQs) in good to excellent yields with high regioselectivity. This heterogeneous copper catalyst can be easily prepared by a simple two-step procedure from commercially available and inexpensive reagents, and recovered by a simple filtration and reused for at least 10 times without any decrease in activity.